Clinical and neurophysiological study of the effects of multiple doses of artemisinin on brain-stem function in Vietnamese patients. - Kissinger, E; Hien, T; Hung, N; Nam, N; Tuyen, N; Dinh, B; Mann, C; Phu, N; Loc, P; Simpson, J; White, N; Farrar, J (2000)
The qinghaosu (artemisinin) group of drugs is the most important new class of antimalarials developed in the last fifty years. Although there has been no clinical evidence of neurotoxicity, an unusual pattern of damage to specific brain-stem nuclei has been reported in experimental animals receiving high doses of arteether or artemether. Detailed clinical examinations, audiometry, and brain stem auditory evoked potentials (BSAEPs) were assessed in 242 Vietnamese subjects who had previously received up to 21 antimalarial treatment courses of artemisinin or artesunate alone and 108 controls from the same location who had not received these drugs. There was no evidence of a drug effect on the clinical or neurophysiological parameters assessed. In this population there was no clinical or neurophysiological evidence of brain-stem toxicity that could be attributed to exposure to artemisinin or artesunate.